SISTEM PEMANTAUAN KELEMBABAN SUHU DAN KELEMBABAN DENGAN ARDUINO R3 DAN DHT 11 - Sonny Rumalutur; Alimuddin Mappa (Electro Luceat, 2019)
This study discusses how to design an AC (Air Conditioner) system that can work based on the temperature and humidity of the room that is regulated by a system that uses Arduino UNO as a controller. Meanwhile, to measure the temperature and humidity of the room temperature by using a DHT sensor 11. PWM (Pluse Widht Modulation) signal from the microcontroller is used to set the relay driver so that the AC (air conditioner) can be on in accordance with the programmed with Arduino uno. AC (air conditioner) will be on as long as the temperature is still above 220C and will be off if the temperature has passed 220C and the duration of AC (air conditioner) on and off is determined by the temperature and humidity in the room.